1999
DOI: 10.1046/j.1365-2249.1999.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's β-amyloid peptides can activate the early components of complement classical pathway in a C1q-independent manner

Abstract: beta-Amyloid (beta-A) accumulates in the brain of patients with Alzheimer's disease (AD) and is presumably involved in the pathogenesis of this disease, on account of its neurotoxicity and complement-activating ability. Although assembly of beta-A in particular aggregates seems to be crucial, soluble non-fibrillar beta-A may also be involved. Non-fibrillar beta-A does not bind C1q, so we investigated alternative mechanisms of beta-A-dependent complement activation in vitro. On incubation with normal human plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…These findings are in agreement with in vitro studies indicating that Aβ and tau protein, the major components in SPs and NFTs, can fully activate human complement [42,68-71]. Although the above studies suggested that complement is activated principally by the aggregated forms of Aβ and tau, soluble, non-fibrillar Aβ may also be capable of activating complement [72]. In contrast to the robust staining of complement proteins in mature plaques, immunoreactivity to these proteins in diffuse plaques has generally been below the level of detection, though it has been reported in some studies [36,73,74].…”
Section: Introductionsupporting
confidence: 89%
“…These findings are in agreement with in vitro studies indicating that Aβ and tau protein, the major components in SPs and NFTs, can fully activate human complement [42,68-71]. Although the above studies suggested that complement is activated principally by the aggregated forms of Aβ and tau, soluble, non-fibrillar Aβ may also be capable of activating complement [72]. In contrast to the robust staining of complement proteins in mature plaques, immunoreactivity to these proteins in diffuse plaques has generally been below the level of detection, though it has been reported in some studies [36,73,74].…”
Section: Introductionsupporting
confidence: 89%
“…It has been reported that C1 activation can occur through interaction with proteases of the blood-clotting cascade (35,36). Although the physiological significance of this mechanism is unclear, it may be speculated also to contribute to the observed difference in the activation of rMASP-2 and natural MASP-2 presented in the form of MBL-deficient serum.…”
Section: Discussionmentioning
confidence: 97%
“…Together with the high levels of cleaved high molecular weight kininogen (HMWK) found in AD CSF samples, this suggests that A may serve as an initiating factor for contact activation in AD brains [221]. The Ainduced FXII activation can subsequently lead to activation of HMWK, and to activation of C1s and C4, independent of C1q, as it was shown also to occur in C1q deficient plasma in vitro [222]. A study with baboons that were treated with a monoclonal antibody that inhibits F XII activation, indicated that Factor XII -dependent activation of CP can also occur in vivo [223].…”
Section: Pivotal Role For C1-inh: Regulation Of Complement and Coagulmentioning
confidence: 97%